Deflection of jets induced by jet-cloud interactions - Mendoza, S; Longair, MS (2002)
Non-relativistic and relativistic models in which astrophysical jets are deflected on passing through an isothermal high density region are analysed. The criteria for the stability of jets to be affected by the formation of internal shocks are discussed.